1985
DOI: 10.1159/000242099
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure: Abnormalities in Placental Growth and Fetal Amino Acid Uptake in the Rat

Abstract: On day 20 of gestation, after ethanol feeding (27% ethanol calories, 25% protein), placental weights, DNA, RNA and water content were greater than in controls pair-fed an isocaloric diet without ethanol or those ad lib fed a pellet diet of similar composition. Rat litter size and fetal body, liver and brain weights were similar in all groups. In vivo fetal amino acid accumulation was significantly lower after alcohol exposure despite similar placental uptake. These results indicate that both placental hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…In these respects, our FAE animal model exhibits a pattern similar to these models of fetal origins of adult disease. The present study also confirmed previous findings of increased placental weight (18,20) and low birth weight (1,25,26) of FAE offspring. It is of interest that this lower weight in the FAE fetus coupled with a lower body weight of the FAE dam occurred despite the similar caloric consumption of FAE and PF dams.…”
Section: Discussionsupporting
confidence: 93%
“…In these respects, our FAE animal model exhibits a pattern similar to these models of fetal origins of adult disease. The present study also confirmed previous findings of increased placental weight (18,20) and low birth weight (1,25,26) of FAE offspring. It is of interest that this lower weight in the FAE fetus coupled with a lower body weight of the FAE dam occurred despite the similar caloric consumption of FAE and PF dams.…”
Section: Discussionsupporting
confidence: 93%
“…Long-term exposure to alcohol prior to and throughout gestation affects the structure and size of the placenta (Amankwah and Kaufmann, 1984;Padmanabhan, 1985;Eguchi et al, 1989;Jollie, 1990). Such changes in placental structure may affect the transport of nutrients from the mother to the fetus (Lin, 1981;Gordon et al, 1985;Fisher et al, 1986;Snyder et al, 1986). In most of these experiments, alcohol exposure began after the onset of pregnancy or was continued into the gestational period, and therefore it is uncertain whether similar placental effects may be induced by alcohol exposure limited to the time prior to pregnancy onset.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported [3] that the placental dry weight is also increased, and there is evi dence [4] that the enlargement represented placental hyperplasia, rather than hypertro phic changes. However, the histology of the enlarged placentas has not been examined to see whether the tissue changes are such as to account for the reduction in placental blood flow and nutrient transport.…”
Section: Introductionmentioning
confidence: 97%
“…The consumption of large amounts of al cohol during pregnancy is associated, in hu mans and experimental animals, with fetal and neonatal retarded growth and develop ment [1,2], It has been noted that the term placentas of alcohol-exposed rats are signifi cantly heavier than those of controls, in spite of the smaller size of the fetuses [3,4], The significance of the placental enlargement is not clear, although it has been suggested [5] that it represents a compensatory adaptation to a reduced nutrient supply to the placenta. There is some evidence for a reduction in the supply of glucose and amino acids from the mother to the fetus [6][7][8], and blood flow to the placenta on day 20 has been shown to be reduced in rats consuming alcohol through out gestation [3].…”
Section: Introductionmentioning
confidence: 99%